Effect of lactic acid on the meat quality properties and the taste of pork Serratus ventralis muscle - Grajales-Lagunes, Alicia; Rivera-Bautista, Cecilia; Ruiz-Cabrera, Miguel; Gonzalez-Garcia, Raul; Ramirez-Telles, Jorge; Abud-Archila, Miguel (Agricultural and Food Science, 2012)
In this work was evaluated the effect of lactic acid treatment method in pork Serratus ventralis muscle on meat quality parameters pH, color, weight loss, cooking loss, hardness, and taste. The treatment was performed by immersing the sample in lactic acid solutions at two concentrations (1 and 3% v v-1) for 1 and 3 min., immediately the samples were stored at 4 °C during 7 days. The taste was evaluated employing trained and untrained judges. Only hardness, weight loss and cooking loss, were affected by lactic acid concentration (p<0.05). The perception of lactic acid taste to trained judges was higher in samples of major concentration and immersion time. To untrained judges the sample treated with 3% lactic acid for 1 minute, had the best acceptation. Both judges reported that the taste of meat was delicious. Therefore, lactic acid treatment may be an alternative to extend pork shelf life.